Immunotherapy rechallenge after nivolumab treatment in advanced non-small cell lung cancer in the real-world setting: A national data base analysis. (February 2020) - Giaj Levra, Matteo; Cotté, François-Emery; Corre, Romain; Calvet, Christophe; Gaudin, Anne-Françoise; Penrod, John R.; Grumberg, Valentine; Jouaneton, Baptiste; Jolivel, Ronan; Assié, Jean-Baptiste; Chouaïd, Christos
Abstract: Objectives: Nivolumab is now a reference treatment for patients with advanced non-small cell lung cancer (NSCLC) after failure of prior platinum-based chemotherapy. Little data are available on treatment approaches following discontinuation of nivolumab and on the interest of a second course of immunotherapy after nivolumab discontinuation. The aims of this study were to describe treatment pathways following nivolumab discontinuation and to describe survival following retreatment with immunotherapy. Materials and methods: The analysis includes all patients with NSCLC recorded in a national hospital database, starting nivolumab in 2015-2016. Nivolumab treatment was considered discontinued if ≥3 infusions were missed. Patients starting a second course of PD-1 inhibitor following nivolumab discontinuation were analysed according to the duration of their initial nivolumab treatment course. Results: 10, 452 patients were included (71 % men; mean age: 63.8 ± 9.6 years; squamous histology: 44 %). Median nivolumab treatment duration was 2.8 months [IQR :1.4–6.9]. Median OS was 11.5 months [95 %CI: 11.1–11.9]; 5118 (53.4 %) patients received post nivolumab therapy lines: 1517 (29.6 %) of these received a second course of PD-1 inhibitor, either after a treatment-free interval (resumption: n = 1127) or after intervening chemotherapy (rechallenge: n = 390). Median OS after nivolumab discontinuation was 15.0 months [13.9–16.7] in the resumption group and 18.4 months [14.8–21.9] in the rechallenge group. Median OS was significantly longer in patients with an initial nivolumab treatment duration ≥3 months. Conclusion: In this real-world setting, outcome after retreatment with a PD-1 inhibitor following a first course of nivolumab was significantly better in patients with a longer duration of initial nivolumab treatment.